Experimental study of the energy impact of a single irradiation with standard laser power and duration parameters on the microcirculatory bed of the dermis - Polkovnikova , K.V.; Konoplitskyi , V.S.; Fomina , L.V.; Korobko , Yu.Ye. (Морфологія / Morphologia / Morfologìâ, 2025)
Topicality. The high efficacy and safety profile of laser therapy allows treatment to be initiated at the earliest stages of disease in patients of different age groups, including pediatric practice. Objective. To evaluate morphological alterations in the microcirculatory vessels of the dermis after session of laser irradiation with standard energy and exposure parameters, and to correlate these changes with the dynamics of skin purpura involution. Object of the study – morphometric changes of the dermal microcirculatory bed in guinea pigs and their alterations under the influence of laser irradiation. Methods. Histological structure and tissue responses of the skin were studied after sequential laser exposure at 30 minutes, 60 minutes, and 90 minutes. Experiments were carried out on guinea pigs, since the morphological structure of their skin is close to that of humans. The authors declare no conflict of interest. Results. The analysis of morphometric parameters of the dermal microcirculatory component revealed a direct correlation with the relative area of stromal edema, which represents one of the key morphological features of purpura. It was established that stromal edema increased despite the gradual reduction of visible purpura manifestations, indicating an inverse relationship between superficial clinical signs and deeper structural alterations. At 60 minutes after irradiation, more pronounced vascular congestion and perivascular edema with erythrocyte stasis were observed, accompanied by minor per diapedesis hemorrhages, reactive inflammatory infiltration, and damage to connective tissue elements. Conclusion. The comparison of purpura involution dynamics with morphological and morphometric vascular changes demonstrates rapid progression of pathological alterations into deeper dermal layers already at early observation periods following irradiation. The findings confirm the possibility of cyclic pathological changes in dermal structures, particularly in the microcirculatory and vascular compartments, during laser therapy sessions.